Penerapan Metode Inkuiri dalam Pengajaran Pendidikan Agama Islam di SDN 011 Sangatta Utara - Paramita, Laura; Wardan, Khusnul (Indra Institute Research & Publication, 2024)
This research aims to analyze the application of the inquiry method in Islamic Religious Education (PAI) learning at SDN 011 Sangatta Utara, East Kutai Regency. This research uses a qualitative approach with case study-type data collection techniques through observation, interviews and documentation. The research focuses on students in grades IV and V, consisting of 30-35 students per class. The results of the study show that the application of the inquiry method at SDN 011 Sangatta Utara has started to run well, where the teacher acts as a facilitator in guiding students through the stages of inquiry such as asking stimulating questions, conducting investigations, and repeating the results. Students actively participate in the learning process, especially in group discussions and presentations. However, some students still have difficulty understanding abstract concepts and need more intensive guidance from the teacher. The main obstacles found in implementing the inquiry method include time constraints, varying student abilities, and limitations in supporting facilities such as internet access. However, the inquiry method has been proven to have a positive impact on increasing students' understanding of PAI concepts and critical thinking skills. This research suggests the need for improved facilities and additional guidance for students who need it so that the application of inquiry methods can be more optimal.